2007
DOI: 10.1200/jco.2007.11.1005
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ovarian Stromal Cell Tumors

Abstract: Surgery remains the most effective treatment for ovarian stromal tumors and, whenever feasible, for relapsing disease. Platinum-based chemotherapy is currently used in metastatic or recurrent tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
276
4
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(309 citation statements)
references
References 60 publications
8
276
4
21
Order By: Relevance
“…Multiple granulosa cell dysfunctions lead to disordered ovulatory and ovarian function [1]. Moreover, granulosa cell tumors (GCTs) are serious ovarian neoplasms that can occur in women of all ages [2]. As most malignant ovarian tumors are epithelial in origin, most studies of ovarian cancer do not include GCTs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple granulosa cell dysfunctions lead to disordered ovulatory and ovarian function [1]. Moreover, granulosa cell tumors (GCTs) are serious ovarian neoplasms that can occur in women of all ages [2]. As most malignant ovarian tumors are epithelial in origin, most studies of ovarian cancer do not include GCTs [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are no data to support any kind of postoperative adjuvant treatment for patients with stage I GCTs, given the indolent nature of these neoplasms and the overall good prognosis [11]. One of the patients was classified as FIGO 1c after restaging.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with stage I disease who underwent adequate staging procedure have a very low risk of recurrence [11]. If disease was not staged at first surgery, a restaging intervention should be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If metastatic, adequate cytoreduction is the mainstay of treatment. If the patient is young and the disease is confined to one ovary, conservative surgery should be performed [96,97].…”
Section: Management Of Granulosa Cell Tumorsmentioning
confidence: 99%